2002
DOI: 10.5194/aab-45-575-2002
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous regulation of the hypothalamic-pituitary-adrenal axis and its impact on fertility, immunity, metabolism and animal welfare – a review

Abstract: The paper reviews mechanisms of neuronal control of the hypothalamic-pituitary-adrenal (HPA) axis with a view on its impact on performance and welfare. The limbic hippocampal and amygdaloid input to the paraventricular hypothalamic nucleus constitutes the basic intracerebral axis by which emotional stimuli affect the stress response. This axis is the backbone of the HPA feedback loop where hippocampus and amygdala are plastic elements and add the ability of experience dependent adaptation and (emotional) learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 144 publications
(129 reference statements)
0
38
0
9
Order By: Relevance
“…The detrimental effects of heat stress are the suppressed intensity of oestrus, a reduced magnitude of the preovulatory luteinizing hormone (LH) surge, decreased secretion of luteal progesterone, altered ovarian follicular development, decreased embryo development and lower fertility (KANITZ et al 2001, AL-KATANANI et al 2002, MANTEUFFEL 2002, WILLARD et al 2003. Negative energy balance due to heat stress leads to reduced LH secretion and anovulation in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of heat stress are the suppressed intensity of oestrus, a reduced magnitude of the preovulatory luteinizing hormone (LH) surge, decreased secretion of luteal progesterone, altered ovarian follicular development, decreased embryo development and lower fertility (KANITZ et al 2001, AL-KATANANI et al 2002, MANTEUFFEL 2002, WILLARD et al 2003. Negative energy balance due to heat stress leads to reduced LH secretion and anovulation in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a deficiency of immune system has a negative effect on somatic cell count in milk. Manteuffel (2002) summarising the regulation of HPA axis and its impact on metabolism and animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, condições de estresse como o reagrupamento de lotes pode ter consequências significativas na função imunológica do animal (MANTEUFFEL, 2002). Em ratos, o estresse agudo provoca mudanças acentuadas, rápidas e reversíveis na distribuição de leucócitos no sangue periférico (DHABBAR et al, 1996).…”
Section: Critérios Ligados à Sanidadeunclassified